2017
DOI: 10.1177/1321103x17700702
|View full text |Cite
|
Sign up to set email alerts
|

An examination of LGBTQ-inclusive strategies used by practicing music educators

Abstract: The purpose of this research was to examine LGBTQ-inclusive strategies used by practicing music educators in the United States. Participants ( N = 300) in a nonprobabilistic sample completed a survey inquiring as to their comfort using LGBTQ-inclusive strategies in a school music class, their perceptions of barriers to LGBTQ inclusion, and whether they had received training related to LGBTQ issues. Self-identified heterosexual respondents were requested to complete an additional set of questions to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Mr. Ames’ re-thinking of gender in the choral classroom has made him think more globally about safety for queer choral students (Garrett & Spano, 2017; Palkki & Caldwell, 2018): I think transgender students are going to force choir directors to re-think some things that they do. [ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mr. Ames’ re-thinking of gender in the choral classroom has made him think more globally about safety for queer choral students (Garrett & Spano, 2017; Palkki & Caldwell, 2018): I think transgender students are going to force choir directors to re-think some things that they do. [ .…”
Section: Resultsmentioning
confidence: 99%
“…All three participants had significant mentor figures who helped them navigate their trans identity. In each case, at least one of their choir teachers proved influential (Garrett & Spano, 2017; Palkki & Caldwell, 2018). Sara often spoke passionately about her first choir teacher—the one who left for another school district after her sophomore year.…”
Section: Discussionmentioning
confidence: 99%
“…Since schools exist within historical and sociopolitical contexts, these recent developments may put trans students at risk (Miller, 2017). Thus, we feel music teacher educators should prepare preservice teachers to create open and affirming classrooms for all students (Carter, 2011; Garrett & Spano, 2017; Hendricks, Smith, & Stanuch, 2014; Taylor, 2018).…”
Section: Policies and Cultural Contextmentioning
confidence: 99%
“…The student teacher could then examine if/how the school’s gender discourses influence the music classroom. Because music classrooms often are considered safe spaces for members of the LGBTQA community (Garrett & Spano, 2017; Palkki & Caldwell, 2018), this comparison may yield a rich discussion. As discourses and norms around gender in school evolve, music teacher educators can continue to read, listen, and learn while sharing insights with current and former students (via a private Facebook group, e-mail list, etc.…”
Section: Gender-complex Music (Teacher) Educationmentioning
confidence: 99%
“…Authors of research and practical articles on current classroom practices often have observed or concluded that music educators may not receive adequate preparation to teach in ways that are responsive to students’ identities, which can include (dis)ability, race, ethnicity, gender, and sexual orientation (e.g., Garrett & Spano, 2017; Hoffman, 2011; Legette, 2003; Nabb & Balcetis, 2010; Taylor et al, 2020). While some programs may include preparation to teach diverse populations as part of education coursework outside of music teacher education, undergraduate students may have difficulty making connections between their future teaching and coursework that is not music specific (see Conway, 2002, 2012).…”
mentioning
confidence: 99%